SEPT6_TRIM33 Gene Fusion and Mutated TP53 Pathway Associate With Unfavorable Prognosis in Patients With B-Cell Lymphomas - Haiying Fu (Frontiers Media S.A., 2021)
BackgroundMounting studies have sought to identify novel mutation biomarkers having diagnostic and prognostic potentials. Nevertheless, the understanding of the mutated pathways related to development and prognosis of B-cell lymphoma is still lacking. We aimed to comprehensively analyze the mutation alterations in genes of canonical signaling pathways and their impacts on the clinic outcomes of patients with B-cell lymphoma.MethodsCirculating cell-free DNA (cfDNA) samples from 79 patients with B-cell lymphomas were used for targeted sequencing with a 560-gene panel for depicting mutation landscapes and identifying gene fusion events. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses of mutated genes were performed. The associations of mutation status of genes and seven canonical oncogenic pathways with progression-free survival (PFS) were assessed using Kaplan-Meier test and multivariate Cox analysis. The variant allele frequencies (VAFs) of genes in TP53 and Hippo pathways in paired baseline and post-treatment samples from 18 B-cell lymphoma patients were compared. Finally, the associations of identified fusion genes, mutated genes, and pathways with treatment response were evaluated based on objective response rates (ORRs) comparisons of groups.ResultsWe identified 666 mutations from 262 genes in baseline cfDNAs from 79 B-cell lymphoma patients, and found some genes were preferentially mutated in our cohort such as GNAQ, GNAS, H3F3A, DNMT3A, HLA-A, and HLA-B. These frequently mutated genes were significantly associated with negative “regulation of gene expression, epigenetic” and virus infections such as cytomegalovirus, Epstein-Barr virus, human immunodeficiency virus 1 infections. We detected five fusion genes in at least two patients with B-cell lymphoma, and among them, TCF7L2_WT1 gene fusion was most frequently detected in 30.4% of patients (24 of 79 cases). SEPT6_TRIM33 gene fusion, mutated TP53 and Hippo pathways were significantly associated with poor PFS, and SEPT6_TRIM33 fusion gene and mutated TP53 pathway were independent prognostic factors for B-cell lymphoma. A decreased VAF of TP53 p.Y88C and LATS2 p.F972L was detected in patients with complete response to treatments. Moreover, a significant difference in ORR was observed in patients with NPM1_NR4A3 and SEPT6_TRIM33 fusions.ConclusionsSEPT6_TRIM33 gene fusion and mutated TP53 and Hippo pathways may serve as prognostic makers for B-cell lymphoma patients.